Myosin II localization during cytokinesis occurs by a mechanism that does not require its motor domain - Zang, Ji-Hong (The National Academy of Sciences, 1998)
Myosin II generates force for the division of eukaryotic cells. The molecular basis of the spatial and temporal localization of myosin II to the cleavage furrow is unknown, although models often imply that interaction between myosin II and actin filaments is essential. We examined the localization of a chimeric protein that consists of the green fluorescent protein fused to the N terminus of truncated myosin II heavy chain in Dictyostelium cells. This chimera is missing the myosin II motor domain, and it does not bind actin filaments. Surprisingly, it still localizes to the cleavage furrow region during cytokinesis. These results indicate that myosin II localization during cytokinesis occurs through a mechanism that does not require it to be the force-generating element or to interact with actin filaments directly.